Effects of semen processing on sperm function: Differences between swim-up and density gradient centrifugation - Hernández Silva, Gabriela (2020)
Purpose: Andrology research has evolved notoriously in the latest years, particularly since male factor contribution to couple infertility has been undoubtedly demonstrated. However, sperm function investigations results are sometimes contradictory, probably as a result of the use of different sperm processing techniques. In this work, we underwent a systematic functional comparison of human sperm samples simultaneously processed by swim-up and density gradient centrifugation, which are the preferred sperm processing methods used in basic and clinical laboratories. Materials and Methods: To compare functional characteristics of sperm isolated by swim-up and density gradient centrifugation followed by incubation at different times under capacitating conditions. Results: Semen samples processed in parallel by these two procedures resulted in sperm preparations with significant differences in redox state, spontaneous intracellular calcium oscillations, hyperactivation, protein tyrosine phosphorylation, and acrosome reaction responsivity to calcium ionophore. Such differences showed time-dependent specific patterns for spontaneous intracellular calcium oscillations, hyperactivation and protein tyrosine phosphorylation. Sperm retrieved by density gradient centrifugation showed more hyperactivation and tyrosine phosphorylation than swim-up sperm, suggesting a higher degree of capacitation. Conclusions: Our results account for functional differences observed in spermatozoa processed with these two methods and therefore may contribute to a better interpretation of outcomes obtained in different laboratories as well as to improve experimental designs aimed to study sperm physiology and fertility potential.